Legalization Of Cyber Notary-Based Notary Deeds As Authentic Deeds - Syafira Paramita (Authentica, 2023)
Legalizing a notarial deed based on a cyber notary as authentic deeds demands the role of notaries in using the concept of a cyber notary to create a fast, precise, and efficient service. However, in this case, the legalization of a cyber-based notary deed does not have perfect proof like authentic deeds. This is because notarial deeds using a cyber notary need to meet the requirements for the authenticity of a deed in Article 1868 of the Civil Code. The problem raised in this study is how authentic the legalization of cyber-based notary deeds is. This research used a juridical normative method. The data collection in this study employed a literature review method and a qualitative method for analyzing the data. The study results show that the legalization of notary deeds using cyber notary does not have perfect proof like authentic deeds because it does not meet the requirements for the authenticity of a deed contained in Article 1868 of the Civil Code. Keywords: Legalization, Authentic Deed, Cyber Notary.